Manor houses, churches and settlements: historical geographies of the Yorkshire Wolds before 1600 - McDonagh, Briony A.K. (2007)
The thesis examines conceptions and experiences of space in later medieval and early modern England with specific reference to the Yorkshire Wolds, a region of low chalk hills in the historic East Riding of Yorkshire. Particular attention is paid to the spatial and symbolic relationships between manor houses, parish churches and rural settlements in the period before c. 1600, and to the ways power was articulated through such a landscape. Chapter IV examines evidence for early church foundations and argues that the geographical relationships between manor houses and churches evident in the Wolds and elsewhere in the fifteenth and sixteenth centuries were not simply an outcome of earlier pre-Conquest practices. The remainder of the thesis explores the continued meaning of these relationships in the later medieval and early modern period, arguing that while landowners might constitute or maintain their power through the architecture of their houses or patronage of nearby churches, these practices were at least partially dependent on the geographical relationships between manor, churches and settlements.